Substantive Constraints on Security Agencies in Cases of Unlawful Arrest under the Iraqi Legal System - Akrami, Ruhollah; Taher, Hussein Yaseen; Ali, Ali Hilu (Journal of Posthumanism, 2025)
This study analyses the substantive constraints imposed on security agencies in cases of unlawful arrest under Iraqi law, aiming to protect human rights and prevent abuse of power. Arrest is a serious procedure that restricts personal liberty, a right safeguarded by the Iraqi Constitution and domestic legislation. The law sets specific conditions under which this right may be limited, balancing the state’s authority to punish with the individual’s right to freedom. An arrest carried out without legal justification constitutes an unlawful infringement on personal liberty and is criminalised to protect individuals from arbitrary detention. Article 322 of the Penal Code punishes any public official or person entrusted with a public service who arrests, imprisons, or detains a person without legal basis with imprisonment for up to seven years or detention. This research focuses on the legal and procedural controls governing arrests, highlighting safeguards designed to protect individuals from unlawful detention. The study finds that Iraqi legislation provides clear constraints to prevent unlawful arrests, but challenges in enforcement reduce their effectiveness. It recommends enhancing judicial oversight, updating laws to comply with international standards, establishing independent monitoring bodies, and providing human rights training for security personnel.